Duration of diabetes, glycemic control, and risk of neuropathy among diabetes population in Indonesia - Al Aska, Andra Agnez; Wardhani, Mira Kusuma (Innovation in Health for Society, 2025)
Diabetic neuropathy is a serious and common complication for individuals with Type 2 Diabetes (T2D). However, there's a scarcity of studies investigating how the duration of diabetes and glycemic control impact the development of neuropathy. This study aimed to examine the effect of diabetes duration and blood glucose levels on the risk of neuropathy in patients with T2D in Surabaya. This was an observational study utilizing a cross-sectional data collection method. Data were gathered from 150 patients between May and July 2023. Patients were categorized based on their diabetes duration (less than 5 years, 5–10 years, and greater than 10 years) and their blood glucose levels (HbA1c less than 7%, 7–10%, and greater than 10%). Neuropathy was assessed using the 10g monofilament test and the Neuropathy Disability Score (NDS). Statistical analysis involved descriptive statistics and logistic regression, with a significance level set at 0.05 for hypothesis testing. The results revealed a significantly higher risk of neuropathy in patients with T2D for more than 10 years (90%) compared to those with T2D for less than 5 years (40%). Similarly, patients with poor blood glucose control (HbA1c greater than 10%) had an 85% chance of developing neuropathy. Whereas only 30% of those with well-controlled blood glucose (HbA1c less than 7%) developed the condition. Logistic regression analysis further confirmed that both a longer diabetes duration and elevated blood glucose levels significantly increase the risk of neuropathy (p<0.05). These findings underscore the critical importance of effective blood glucose management and early neuropathy detection to prevent severe diabetic complications. Furthermore, this study highlights the urgent need for enhanced diabetes education, early screening programs, and improved healthcare strategies across Indonesia to mitigate the burden of diabetic neuropathy. Keywords: Duration of diabetes, endocrinology, glycemic control, innovation in health, type 2 diabetes